Study of the Syntactic Structures of Direct Speech in Spanish and Chinese - Yu, Yang (Sinología hispánica. China Studies Review, 2020)
Quote is one of the general linguistic phenomena. The direct speech and indirect speech are its two primary procedures. As the direct speech is universal and it exists in all languages, in this work we focus on its formal structures in two different languages, the Spanish and the Chinese. The study mainly includes two parts. The first part consists in clarifying theoretical questions about quote from speech acts theory. We illustrate that the minimum unit of the study is utterance, which contains a linguistic statement and a pragmatic modality. The second part is to investigate the direct speech’s formal structures in both languages, such as the syntactic relation (hypotaxis, parataxis or other discursive nature) between the introductory expression and the reproduced part; direct speech’s syntactic variants with a series of pronouns (así-como-cómo) and the different types of the structural superpositions in the direct speech. The contrasts of the direct speech in these two languages mainly reside in the orthography and the position of the reproductive framework. In the end, we can conclude that the characteristic of being universal not only reflects on its use, but also on its formal structures.